PTU-064 Identification of Syne1 and Foxe1 Hypermethylation to improve Diagnosis and Management of Colerectal Neoplasia in Inflammatory Bowel Disease. (4th June 2013) - Papadia, C; Louwagie, J; Rio, P Del; Novelli, M; Atkin, W; Bordi, C; Bassett, P; Forbes, A
Abstract : Introduction: Colitis-associated colorectal cancer (CAC) affects individuals with inflammatory bowel disease (IBD) more often and younger than cancer in the general population. Colonoscopy provides the surveillance gold standard. Changes to surveillance intervals have been made given data demonstrating that endoscopic appearance is an important predictor of future dysplasia or cancer, but adjuvant, non-invasive clinical tools are still warranted to improve surveillance outcomes and to assist in management and interpretation of dysplasia. Methylation markers may be able to do this. Material and methods Methods: using reexpression profiles of colon cancer cell lines, candidate genes were identified; promising markers were tested on tissue using the Base5 methylation-profiling platform. Promoter sequences were linked with gene expression to identify epigenetically silenced genes. Marker candidates were screened using methylation specific PCR assays to assess the methylation status of 2 gene promoters (FOXE1, SYNE1) in biopsies from 93 longstanding IBD patients and 30 healthy controls. Samples included colitis-associated colorectal adenocarcinomas (n = 25); IBD-associated dysplastic lesions (n = 29); adenomas arising on a background of UC (n = 8); samples from IBD patients with no neoplasia (n = 31) and healthy controls (n = 30). Results: The presence of the 2 genes significantly varied between the groups. Both were increasing likely with increased disease severity. Neither occurred in controls, whilst 60% of CAC patients had FOXE1, and 80% of CAC patients had SYNE1. Conclusion: FOXE1- SYNE1 methylation markers panel demonstrated significantly increased expression in neoplastic tissue. Syne1 was highly represented in CAC. Methylation of these promoter genes might be considered a potentially useful pathology marker of neoplasia in longstanding inflammatory bowel disease. Disclosure of Interest: None Declared